Effectiveness of overuse injury prevention programs on upper extremity performance in overhead youth athletes: A systematic review - Lau, R. Y.; Mukherjee, S. (Sports Medicine and Health Science, 2023)
Several targeted upper extremity injury prevention programs have been developed to mitigate the risk of upper extremity overuse injuries among youth athletes in overhead sports; however, their effectiveness on performance outcome measures has not been investigated. This systematic review evaluated the effectiveness of existing upper extremity injury prevention programs that focused on modifying intrinsic risk factors, and performance outcome measures in overhead youth athletes. The secondary aim was to identify the training components of these programs. PubMed, Physiotherapy Evidence Database (PEDro), SPORTDiscus (via EBSCOhost), and Web of Science were searched from January 2000 to November 2020 for studies that implemented training programs or exercises for upper extremity injury prevention among youth athletes in overhead throwing or striking sports. An updated search was conducted from December 2020 to October 2022. A program was deemed effective for a performance outcome measure if significant improvements were observed in the intervention group as compared to the control group. Of the 1 394 studies identified, five studies met the inclusion criteria. The effectiveness of the injury prevention programs on the identified performance outcome measures of strength, mobility, and sport-specific measures were 30.4%, 28.6%, and 22.2%, respectively. The training components targeted were strength, mobility, and plyometrics. Strength was the most common training component and was also the most widely investigated performance outcome measure. Overall, current upper extremity injury prevention programs seem effective at improving performance outcome measures of strength, mobility, and sport-specific outcomes with training components of strength, mobility and plyometrics. Standardized protocols are required for the measurement and reporting of performance outcomes measures, and the reporting of training components.